Equipment utilization on construction sites (case study of large and medium construction firms in Ghana) - Gyan, Alfred Ekow (2011)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for Master of Science degree, 2002